Characterization of PVA cryogel for intravascular ultrasound elasticity imaging - Fromageau, J.; Brusseau, E.; Vray, D.; Gimenez, G.; Delachartre, P. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2003)
The present study characterizes the mechanical properties of polyvinyl alcohol (PVA) cryogel in order to show its utility for intravascular elastography. PVA cryogel becomes harder with an increasing number of freeze-thaw cycles, and Young's modulus and Poisson's ratio are measured for seven samples. Mechanical tests were performed on cylindrical samples with a pressure column and on a hollow cylinder with the calculation of an intravascular elastogram. An image of the Young's modulus was obtained from the elastogram using cylinder geometry properties. Results show the mechanical similitude of PVA cryogel with the biological tissues present in arteries. A good agreement between Young's modulus obtained from pressure column and from elastogram was also observed.